Serial Monitoring of the Physiological Effects of the Standard Pico-Salax® Regimen for Colon Cleansing in Healthy Volunteers. (2012) - Rahman, Adam; Vanner, Stephen J; Baranchuk, Adrian; Hookey, Lawrence C
Abstract : BACKGROUND: Sodium picosulfate/magnesium oxide/citric acid (Pico-Salax, Ferring Inc, Canada) is used widely in Canada and other countries for colon cleansing before colonoscopy. It is a low-volume osmotic/stimulant agent with the potential to deplete intravascular volume and alter electrolyte balance, yet there are little data regarding its effects on these clinically important end points. OBJECTIVE: To serially measure parameters of intravascular volume and electrolyte status in healthy volunteers over a 24 h period using the standard two-sachet dosing. METHODS: Twenty volunteers were given one sachet of Pico-Salax at time 0 h and another sachet 5 h later, as per usual bowel cleansing protocol. Subjects were continually monitored during the first 12 h of the study with postural vital signs, serum electrolytes and electrocardiograms obtained at intervals throughout this initial period and again at 24 h postingestion. RESULTS: No adverse events were reported nor were there any signs of intravascular volume depletion observed. There were decreases in potassium and calcium levels from baseline to 12 h, but these appeared minor and were corrected by 24 h. The proportions of patients with hypermagnesmia at 0 h, 5 h, 12 h and 24 h were 5%, 35%, 35% and 20%, respectively (P<0.05). However, the maximal values were only minimally elevated. Mean serum sodium, phosphate and creatinine levels remained within their respective reference ranges. There was a trend toward an increase in maximum corrected QT intervals from time 0 h (418 ms) to 5 h (430 ms) (P=0.06), but no significant change was seen subsequently at 12 h (419 ms). The subjects tolerated the medication well. The mean number of bowel movements per subject was 8.15 (range four to 15). Subjects consumed a mean (± SD) of 3.49±1.53 L of fluids during the observation period. CONCLUSIONS: The proportion of individuals with hypokalemia, hypocalcemia and hypermagnesemia following two sachets of Pico-Salax is significant, but the magnitude of the changes was not clinically relevant in this relatively small group, and both calcium and potassium levels normalized at 24 h. Nonetheless, this could have implications in patients with pre-existing electrolyte abnormalities and the safety of dosing with more than two sachets.